The welfare state redistribution and the economy : reciprocal altruism, consumer rivalry and second best - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2004)
Democratic countries with substantial inequality and where people believe that success depends on connections and luck induce political support for high tax rates and generous welfare states. Traditional wisdom is that such policies harm the economy, but there is not much evidence that countries with a large welfare state and substantial redistribution have worse economic performance and welfare. One important reason is that governments have been careful to invoke the principles of reciprocity and mutual obligations in the design of the welfare state. Unemployment benefits conditioned on work experience, no misconduct and search effort harm the economy less. Indeed, conditional benefits may even boost employment in an economy with efficiency wages. A second reason is that people care about relative incomes and become unhappy if others earn and consume much more than they do. This explains why people do not seem to get happier, even though societies grow richer and richer. With such consumer rivalry the government wishes to correct for the rat race, even if there is no need for redistribution, by taxing labour. A third reason is that in modern economies many distortions are present and removing one at a time may worsen economic performance. Conversely, increasing tax progression in economies with non-competitive labour markets induces wage moderation and boosts employment. A final reason is that countries with large welfare states typically introduce various progrowth policies as well.
Keywords: J5; J6; H2; H53; 330; mutual obligations; altruism; relative incomes; happiness; redistributive taxation; demand management; second best; design of welfare state; Sozialstaat; Einkommensumverteilung; Wirtschaftswachstum; Wohlfahrtseffekt; Altruismus; Gerechtigkeit; Konsuminterdependenz; Effizienzlohn; Second Best; Theorie